Evaluation of Classical Guidance Programs During the Covid-19 Pandemic at Junior High School: Discrepancy Model - Nurrofifah, Hani; Farozin, Muh.; Mutiara, Asfarina (Jurnal Kajian Bimbingan dan Konseling, 2022)
Guidance and counseling programs are designed to improve education. These programs continue to evolve, especially the classical guidance programs that require adaptation to the current Covid-19 pandemic education system. However, due to a lack of planning, the development and implementation of the classical guidance program in state junior high schools during the Covid-19 pandemic have not been optimal. Thus, this study identifies the performance of the classical guidance program at state junior high schools during the Covid-19 pandemic, using predetermined standards. This study used program evaluation standards and criteria from the Guidelines for Performance-Based Professional School Counselor Evaluation. The guidelines highlight that professional school counselors should carry out classical guidance services using effective learning strategies and classroom management techniques for all counselees based on their needs. These standards and criteria were then formulated into three components to determine the success of the classical guidance program, namely planning, implementing, and evaluating the classical guidance program. The analysis of the evaluation results showed that the classical guidance program during the Covid-19 had not met the standard.